Daily Social Life of Older Adults and Vulnerabilities During the COVID-19 Pandemic - Chen, Jen-Hao (Frontiers in Public Health, 2021)
Introduction: The social integration of older adults is crucial for understanding their risk of infection and mental health during the COVID-19 pandemic. However, older adults’ social lives differ, which means they are not all vulnerable to COVID-19 in the same way. This paper analyzes older adults’ everyday time use and social contacts to inform discussions of older adults’ vulnerabilities during the pandemic. Methods: Using the 2019 American Time Use Survey (N=4256, aged 55 and older), hurdle model regressions were used to examine the relationship between age, gender, and six indicators of the degree of social contact and time use: (1) time alone, (2) time spent with family members, (3) time spent with non-family members, (4) time spent with people in the same household, (5) number of public spaces visited, and (6) time spent in public spaces. Results: Results showed substantial heterogeneity in everyday time use and social contacts. Time in public places gradually decreased from the oldest-old (85 years or older), old-old (75-84 years), to mid-life (55-64 years) adults. The gaps were not explained by age differences in sociodemographic characteristics and social roles. Compared to mid-life adults, young-old and old-old adults’ time with family members decreased but time with non-family members increased. Age differences in social roles over the life course partially explained the differences. Conclusion: Should these patterns of time use and social contacts persist during COVID-19, then such variations in the organization of social life may create different exposure contexts and vulnerabilities to social distancing measures among older adults; such information could help inform interventions to better protect this population.